Unified Theory of Acceptance and Usage of Technology (UTAUT) Model to Predict Health Information System Adoption - Nurhayati, Siti; Anandari, Dian; Ekowati, Wahyu (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
In order to improve the quality and performance of health services, health information systems are one of the most important technologies in health management. This study aims to determine the factors that influence the adoption of nutrition information system by nutrition officers of primary health care by using Unified Theory of Acceptance and Usage of Technology (UTAUT) Model. This research is quantitative research with survey approach, located in 39 primary health care of Banyumas district. Sampling technique using purposive sampling. Respondents are 50 people. The research instrument used questionnaire. Based on regression test results known that factors related to use behaviour is behavioral intention. While the facilitating condition is not related to use behavior. Factors associated with behavioral intention is the performance expectancy, effort expectancy and social influence.